Evaluation of cholesterol metabolism in cerebrotendinous xanthomatosis. Issue 1 (8th July 2015) - Mignarri, Andrea; Magni, Alessandro; Del Puppo, Marina; Gallus, Gian Nicola; Björkhem, Ingemar; Federico, Antonio; Dotti, Maria Teresa
Abstract: Background: Cerebrotendinous xanthomatosis (CTX) is a treatable bile acid disorder caused by mutations of CYP27A1 . The pathogenesis of neurological damage has not been completely explained. Oral chenodeoxycholic acid (CDCA) can lead to clinical stabilization, but in a subgroup of patients the disease progresses despite treatment. In the present study, we aimed at clarifying cholesterol metabolism abnormalities and their response to CDCA treatment, in order to identify reliable diagnostic and prognostic markers and understand if differences exist between stable patients and those with neurological progression. Methods: We enrolled 19 untreated CTX patients and assessed serum profile of bile acids intermediates, oxysterols, cholesterol, lathosterol, and plant sterols. Then we performed a long‐term follow up during CDCA therapy, and compared biochemical data with neurological outcome. Results: We observed increase of cholestanol, 7α‐hydroxy‐4‐cholesten‐3‐one (7αC4), lathosterol, and plant sterols, whereas 27‐hydroxycholesterol (27‐OHC) was extremely low or absent. CDCA treatment at a daily dose of 750 mg normalized all biochemical parameters except for 7αC4 which persisted slightly higher than normal in most patients, and 27‐OHC which was not modified by therapy. Biochemical evaluation did not reveal significant differences between stable and worsening patients. Discussion: Cholestanol and 7αC4 represent important markers for CTX diagnosis and monitoring of therapy. Treatment with CDCA should aim at normalizing serum 7αC4 as well as cholestanol, since 7αC4 better mirrors 7α‐hydroxylation rate and is thought to be correlated with cholestanol accumulation in the brain. Assessment of serum 27‐OHC is a very good tool for biochemical diagnosis at any stage of disease. Lathosterol and plant sterols should be considered as additional markers for diagnosis and monitoring of therapy. Further studies including long‐term assessment of bile acid intermediates in cerebrospinal fluid are needed in patients who show clinical progression despite treatment.